2015
DOI: 10.1080/1350293x.2014.996422
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ perceptions of children's literacy motivation and their home-literacy practices: what's the connection?

Abstract: The purpose of this study was to examine the extent to which parental beliefs about children's literacy motivation is associated with their literacy practices at home. A sample of 315 parents of preschool-aged children participated in the study, and completed a newly developed questionnaire pursuant to the aims of this work. Thus, the construct of literacy motivation in this study is based on parental report. The results of a confirmatory factor analysis, focused on questionnaire items concerning children's mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 54 publications
1
12
0
2
Order By: Relevance
“…For example, Nichols (2002) found that parents of girls tend to believe that their children have more talent in literacy and are less problematic in literacy learning than parents of boys. Similar findings have been reported in recent studies where the parents' perceptions of their children's literacy attitudes were more positive for girls (Baroody & Diamond, 2013;Sackes, Isitan, Avci, & Justice, 2015).…”
Section: Parents' Gendered Views About Literacysupporting
confidence: 90%
“…For example, Nichols (2002) found that parents of girls tend to believe that their children have more talent in literacy and are less problematic in literacy learning than parents of boys. Similar findings have been reported in recent studies where the parents' perceptions of their children's literacy attitudes were more positive for girls (Baroody & Diamond, 2013;Sackes, Isitan, Avci, & Justice, 2015).…”
Section: Parents' Gendered Views About Literacysupporting
confidence: 90%
“…We opted to rely on parents' reports mainly due to ethical issues involving children's participation in online questionnaires. However, as aforementioned, previous research has demonstrated that parents are relevant (Dinkelmann and Buff, 2016) and accurate (Eccles, 2005) sources, for instance in reporting their perception on students' literacy motivation (e.g., Saçkes et al, 2016). Future research could rely on children's perceptions of their own academic motivation and participation in extracurricular activities.…”
Section: Limitationsmentioning
confidence: 90%
“…According to the self-determination theory, the fulfillment of students' psychological needs for competence, autonomy, and relatedness also depend on: (a) the way parents organize the environment (i.e., definitions of rules, guidelines, and expectations); (b) parent autonomy-support and respect for children's perspectives; and (c) the extent to which parents are involved and establish positive, caring relationships with their children (Grolnick et al, 2009). In addition, researchers have relied on reports from significant adults, namely parents and teachers, as reliable sources to assess student motivation and academic performance (e.g., Gilger, 1992;Harris et al, 2006;Saçkes et al, 2016;Allerhand, 2018;Owens et al, 2020).…”
Section: Academic Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Keterampilan keaksaraan berkembang selama tahun-tahun awal prasekolah yang dipengaruhi dari sifat serta tingkat praktik keaksaraan di rumah (Saçkes, Işıtan, Avci, & Justice, 2016). Kemudian, ketika mulai memasuki taman kanak-kanak mereka sudah mulai memiliki keterampilan baca tulis (Pyle, Prioletta, et al, 2018).…”
Section: Strategi Pedagogisunclassified